Evaluation of Creep Properties in Anode Materials for Solid Oxide Fuel Cells by Using Small Punch Testing Method. (10th July 2019) - Huang, Yihui; Sato, Kazuhisa; Kumada, Keigo; Hashida, Toshiyuki
Abstract : To assess the mechanical reliability and durability of solid oxide fuel cells (SOFCs), a suitable creep test method needs to be developed. The objective of this study is to examine the potential of small punch (SP) method as a simple creep testing method for SOFCs. In this study, the creep properties of Ni-YSZ composites were evaluated at temperatures of 800-900˚C, and at stresses of 47.3 to 89.8 MPa under 1% hydrogen environment. The obtained creep curves by the SP method showed three stages: initial transition creep, secondary creep, and tertiary stages. The central displacement versus time data obtained by the SP method was found to be characterized by a power law relationship. Even though quantitative comparisons need to be made with conventional methods, the above result suggests the usefulness of the SP methods for characterizing the creep properties in constituent materials of SOFCs.